(3HMhK JWHjbjIs - (3GMeO GdHOhj eMeO(B, (3GdTQjYjs ((3GdbGgQI(B:s (3OGQ GdacQ GdYQHj(B,s, 1996)
(3jYO gPG GdcJGH ef GdOQGSGJ GdQGFOI GdJj JgJe HbVGjG GdYeQGf GdQjaj aj GdefWbI GdYQHjI hGf cGf bO SHbJg HYV GdOQGSGJ aj faS GdeLGd GdG efgLjI GdOQGSI hGSdhH GdeYGdLI hWQjbI GdWQM aj gPg GdHMhK LGAJ eNJdaI cKjQG YeG SHbJgG aYdi GdQZe ef Cf ddYeQGf GdQjaj GdVhA Ydi JHGjf GfeGW GdMjI GdEbJUGOjI GdQjajI hCKQ Pdc Ydi GdHfjI GdYeQGfjI aj HYV GdHdGO GdhWf GdYQHj cGf Gge GSHGH cJGHI gJg GdHMhK(B.s
Keywords: (3GdLZQGajG GdHTQjIs; (3GdMjGI GdQjajIs; (3YeQGf Qjaj (B- (3LZQGajGs